Estimates of genetic variances and relationship among traits associated with stem borer resistance in maize (Zea mays L.) - Oloyede-Kamiyo, Q.; Ajala, S.; Akoroda, M.O. (Elsevier, 2014)
Cassava mosaic disease (CMD), caused by different species of cassava mosaic geminiviruses (CMGs), is themost important disease of cassava in Africa and the Indian sub-continent. The cultivated cassava speciesis protected from CMD by polygenic resistance introgressed from the wild species Manihot glaziovii anda dominant monogenic type of resistance, named CMD2, discovered in African landraces. The ability ofthe monogenic resistance to confer high levels of resistance in different genetic backgrounds has ledrecently to its extensive usage in breeding across Africa as well as pre-emptive breeding in Latin Amer-ica. However, most of the landraces carrying the monogenic resistance are morphologically very similarand come from a geographically restricted area of West Africa, raising the possibility that the diversityof the single-gene resistance could be very limited, or even located at a single locus. Several mappingstudies, employing bulk segregant analysis, in different genetic backgrounds have reported additionalmolecular markers linked to supposedly new resistance genes. However, it is not possible to tell if theseare indeed new genes in the absence adequate genetic map framework or allelism tests. To address thisimportant question, a high-density single nucleotide polymorphism (SNP) map of cassava was developedthrough genotyping-by-sequencing a bi-parental mapping population (N = 180) that segregates for thedominant monogenic resistance to CMD. Virus screening using PCR showed that CMD symptoms andpresence of virus were strongly correlated (r = 0.98). Genome-wide scan and high-resolution compositeinterval mapping using 6756 SNPs uncovered a single locus with large effect (R2= 0.74). Projection ofthe previously published resistance-linked microsatellite markers showed that they co-occurred in thesame chromosomal location surrounding the presently mapped resistance locus. Moreover, their relativedistance to the mapped resistance locus correlated with the reported degree of linkage with the resis-tance phenotype. Cluster analysis of the landraces first shown to have this type of resistance revealedthat they are very closely related, if not identical. These findings suggest that there is a single source ofmonogenic resistance in the crop’s genepool tracing back to a common ancestral clone. In the absenceof further resistance diversification, the long-term effectiveness of the single gene resistance is knownto be precarious, given the potential to be overcome by CMGs due to their fast-paced evolutionary rate.However, combining the quantitative with the qualitative type of resistance may ensure that this resis-tance gene continues to offer protection to cassava, a crop that is depended upon by millions of peoplein Africa against the devastating onslaught of CMGs.